Calcium-Induced Activity and Folding of a Repeat in Toxin Lipase from Antarctic Pseudomonas fluorescens Strain AMS8 - Nur Shidaa Mohd Ali; Abu Bakar Salleh; Raja Noor Zaliha Raja Abd Rahman; Thean Chor Leow; Mohd Shukuri Mohamad Ali (Toxins, 2020)
It is hypothesized that the Ca2+ ions were involved in the activity, folding and stabilization of many protein structures. Many of these proteins contain repeat in toxin (RTX) motifs. AMS8 lipase from Antarctic Pseudomonas fluorescens strain AMS8 was found to have three RTX motifs. So, this research aimed to examine the influence of Ca2+ ion towards the activity and folding of AMS8 lipase through various biophysical characterizations. The results showed that CaCl2 increased lipase activity. The far-UV circular dichroism (CD) and Fourier-transform infrared (FTIR) analysis suggested that the secondary structure content was improved with the addition of CaCl2. Fluorescence spectroscopy analysis showed that the presence of CaCl2 increased protein folding and compactness. Dynamic light scattering (DLS) analysis suggested that AMS8 lipase became aggregated at a high concentration of CaCl2.The binding constant (Kd) value from the isothermal titration calorimetry (ITC) analysis proved that the Ca2+ ion was tightly bound to the AMS8 lipase. In conclusion, Ca2+ ions play crucial roles in the activity and folding of the AMS8 lipase. Calcium binding to RTX nonapeptide repeats sequences will induced the formation and folding of the RTX parallel β-roll motif repeat structure.